ANALISIS TINGKAT PENDAPATAN PETANI KAWASAN RUMAH PANGAN LESTARI (KRPL) DI KOTA PEKANBARU PROVINSI RIAU - Amran, Leo; Tarumun, Suardi; ', Eliza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Sustainable food home area (KRPL) is goverment program to increasing of consume of society food with basis of farmer addition income. The porpose of this research is to analysis farming income of KRPL in Pekanbaru city and to analysis farming revenue contribution of KRPL yard to ward house hould income in Pekanbaru city. The metodh used to taking of the sample is proportional random sampling. Total of sample in this research area 17 sample of KRPL. The data analysis used in this research area farming analysis and farming revenue contribution analysis toward income house hould. Toal revenue of KRPL farming yard is Rp.2.568.000 per plant seasen or Rp.151.059 per farmer. Contribution average has given KRPL program to member of KRPL income in Pekanbaru city 2% or Rp.50.773 per farmer. Â Keywords: KRPL Program, Household Income, Pekanbaru City.